Analysis of pion production data measured by HADES in proton-proton collisions at 1.25 GeV - HADES collaboration (99 authors) (2017)
Baryon resonance production in proton-proton collisions at a kinetic beam energy of 1.25 GeV is investigated. The multi-differential data were measured by the HADES Collaboration. Exclusive channels with one pion in the final state ($npπ^+$ and $ppπ^0$ were put to extended studies based on various observables in the framework of a one-pion exchange model and with solutions obtained within the framework of a partial wave analysis (PWA) of the Bonn-Gatchina group. The results of the PWA confirm the dominant contribution of the $Δ(1232)$, yet with a sizable impact of the $N(1440)$ and non-resonant partial waves.